A Study on Congenital Malformations - Saeid, Khalid Hhamyd Muhamad; Aleany, Luy Muhamad; Yaequb, Amal Muhamad (Al-Mukhtar Journal of Sciences, 1997)
This study was conducted on births registered at Thowr a hospital. El-Beida for a period of twelve months, approximately. The number of births registered at the maternity ward was 4513. The study aimed to determining the extent of distribution of congenital malformations in neonates hoping to shed some light on some of the factors causing these malformation. Results of this study have uncovered the presence of various congenital malformations with an average of 5 malformations per 1000 live births. This is considered a high percentage albeit. The possibility that it may not represent the actual situation, taking into account the outward births together with cases of abortion, sillbirths and the abnormalities that might not be manifested at the time of birth. The malformation observed induced Downs Syndrome, Anencephaly, Spina Bifid, Polydactyly, Thoracopagus and other malformations. Analysis of the results has revealed that the percentage of malformations increased in cases of inbreeding where the percentage reached 30% of the total. besides, mother's age has an important role in the possibility of recurrence of some of the malformations, such as Down's Sundrome. This variation in congenital malformations indicates the presence of similar variations in the environmental and genetic causative agents and their cross-reactions.